A participação da Rede Municipal de Educação em Altamira na rede de enfrentamento da violência sexual contra crianças e adolescentes - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Among the most diverse social problems, the abuse and sexual exploitation of children and adolescents demands beyond a series of theoretical and conceptual reflections, requires a practical action regarding their coping. From this perspective, the problem addressed in this research had as its central question: How is the articulation of the Altamira municipal education network in the confrontation network to the existing sexual violence in the municipality? The research aims to analyze the participation of the Altamira Municipal Education Network in the network to confront sexual violence against children and adolescents. The methodology adopted is of a qualitative character, through a case study of the Altamira Municipal Education Network, based on a documental analysis and interviews with the Secretary of Education and / or the Education Director of the Municipal Secretary of Education and Education. The main representative entities of the protection network against sexual violence against children and adolescents in the municipality The data were analyzed through documentary analysis, which reveals that the Municipal Education Network has no action projects to address the sexual violence of children and adolescents, and when participating in any project is always in partnership with other entities belonging to protection net. The actions take place, but in isolation and practiced by schools and teachers, which weakens the confrontation, as it does not lead to a necessary articulation capable of implementing the policy of protection and defense against sexual violence of children and adolescents.
Keywords: Escola; Rede de proteção; Violência sexual; Rede de ensino